Ritual, Violence, and the Fall of the Classic Maya Kings - Schwake, Sonja A.; Houk, Brett A. (Brett Alan), 1967-; Iannone, Gyles (Book collections on Project MUSE., 2016)
This volume explores the links between the declining prosperity of the Late to Terminal Classic period and the erosion of kingly legitimacy. Exploring issues such as the rise of inflation, greater demand of tax and tribute, deforestation due to over-population, and drought conditions, the essayists examine what happens to a society when the king, who should be appeasing the gods, is seen as the problem.